Math, asked by shreyanshs147, 10 months ago

Solve please
First correct answer gets brainliest.​

Attachments:

Answers

Answered by deepi39
0

Step-by-step explanation:

LHS=

tan

2

θ−1

tan

2

θ

+

sec

2

θ−cosec

2

θ

cosec

2

θ

= \frac{\frac{sin^{2}\theta}{cos^{2}\theta}}{\frac{sin^{2}\theta}{cos^{2}\theta}-1} + \frac{\frac{1}{sin^{2}\theta}}{\frac{1}{cos^{2}\theta} - \frac{1}{sin^{2}\theta}}=

cos

2

θ

sin

2

θ

−1

cos

2

θ

sin

2

θ

+

cos

2

θ

1

sin

2

θ

1

sin

2

θ

1

= \frac{\frac{sin^{2}\theta}{cos^{2}\theta}}{\frac{sin^{2}\theta-cos^{2}\theta}{sin^{2}\theta cos^{2}\theta}} + \frac{\frac{1}{sin^{2}\theta}}{\frac{sin^{2}\theta-cos^{2}\theta}{sin^{2}\theta cos^{2}\theta }}=

sin

2

θcos

2

θ

sin

2

θ−cos

2

θ

cos

2

θ

sin

2

θ

+

sin

2

θcos

2

θ

sin

2

θ−cos

2

θ

sin

2

θ

1

= \frac{ sin^{2}\theta cos^{2}\theta}{cos^{2}\theta(sin^{2}\theta - cos^{2}\theta)} + \frac{ sin^{2}\theta cos^{2}\theta}{sin^{2}\theta(sin^{2}\theta-cos^{2}\theta}=

cos

2

θ(sin

2

θ−cos

2

θ)

sin

2

θcos

2

θ

+

sin

2

θ(sin

2

θ−cos

2

θ

sin

2

θcos

2

θ

= \frac{ sin^{2}\theta}{sin^{2}\theta-cos^{2}\theta} + \frac{ cos^{2}\theta}{sin^{2}\theta-cos^{2}\theta}=

sin

2

θ−cos

2

θ

sin

2

θ

+

sin

2

θ−cos

2

θ

cos

2

θ

= \frac{ sin^{2}\theta + cos^{2}\theta}{sin^{2}\theta - cos^{2}\theta}=

sin

2

θ−cos

2

θ

sin

2

θ+cos

2

θ

\begin{gathered}= \frac{1}{sin^{2}\theta - cos^{2}\theta} \\= RHS\end{gathered}

=

sin

2

θ−cos

2

θ

1

=RHS

Therefore.,

\red {\frac{tan^{2}\theta}{tan^{2}\theta-1} + \frac{cosec^{2}\theta}{sec^{2}\theta-cosec^{2}\theta}}

tan

2

θ−1

tan

2

θ

+

sec

2

θ−cosec

2

θ

cosec

2

θ

\green {= \frac{1}{sin^{2}\theta - cos^{2}\theta}}=

sin

2

θ−cos

2

θ

1

Answered by afra1278
0
Deepi 39 answer is the right answer
Similar questions